Peran pondok pesantren dalam melestarikan adat istiadat islam di jawa - Islami, Muhammad Shokhikhul (Maliki Interdisciplinary Journal, 2025)
The significance of Islamic boarding schools in Java in upholding Islamic traditions in the face of modernization and globalization is covered in this article. As traditional Islamic educational establishments, Islamic boarding schools have historically served as hubs for maintaining regional culture while maintaining an Islamic vibe. The history and evolution of Islamic boarding schools are examined in this article, along with examples of preserved customs (such as the Prophet's birthday, Isra Miraj, grave pilgrimages, salvation, and Muslim clothing traditions) and preservation techniques (such as oral traditions, Islamic arts and culture, religious practices, and yellow book learning). Along with the future potential of Islamic boarding schools via adaptation, innovation, collaboration, and identity building, the difficulties that these institutions face—such as modernization, the impact of other cultures, and limited resources—are also covered. According to the article's conclusion, Islamic boarding schools may remain significant foundations in society because of their identity and principles.